Postmenopausal weight change and incidence of fracture: post hoc findings from Women's Health Initiative Observational Study and Clinical Trials. (27th January 2015) - Crandall, Carolyn J; Yildiz, Vedat O; Wactawski-Wende, Jean; Johnson, Karen C; Chen, Zhao; Going, Scott B; Wright, Nicole C; Cauley, Jane A
Abstract : Objectives To determine associations between postmenopausal change in body weight and incidence of fracture and associations between voluntary and involuntary weight loss and risk of fracture. Design Post hoc analysis of data from the Women's Health Initiative Observational Study and Clinical Trials. Setting 40 clinical centers in the United States. Participants 120 566 postmenopausal women, aged 50-79 at baseline (1993-98), followed through 2013 (mean fracture follow-up duration 11 years from baseline). Exposures Annualized percentage change in measured body weight from baseline to year 3, classified as stable (<5% change), weight loss (≥5%), or weight gain (≥5%). Self assessment of whether weight loss was intentional or unintentional. Cox proportional hazards regression models were adjusted for age, race/ethnicity, baseline body mass index (BMI), smoking, alcohol intake, level of physical activity, energy expenditure, calcium and vitamin D intake, physical function score, oophorectomy, hysterectomy, previous fracture, comorbidity score, and drug use. Main outcomes Incident self reported fractures of the upper limbs, lower limbs, and central body; hip fractures confirmed by medical records. Results Mean participant age was 63.3. Mean annualized percent weight change was 0.30% (95% confidence interval 0.28 to 0.32). Overall, 79 279 (65.6%) had stable weight; 18 266 (15.2%) lost weight; and 23 021 (19.0%) gained weight. Compared with stable weight, weight loss was associated with a 65% higher incidence rates of fracture in hip (adjusted hazard ratio 1.65, 95% confidence interval 1.49 to 1.82), upper limb (1.09, 1.03 to 1.16), and central body (1.30, 1.20 to 1.39); weight gain was associated with higher incidence rates of fracture in upper limb (1.10, 1.05 to 1.18) and lower limb (1.18, 1.12 to 1.25). Compared with stable weight, unintentional weight loss was associated with a 33% higher incidence rates of hip fracture (1.33, 1.19 to 1.47) and increased incidence rates of vertebral fracture (1.16, 1.06 to 1.26); intentional weight loss was associated with increased incidence rates of lower limb fracture (1.11, 1.05 to 1.17) and decreased incidence of hip fracture (0.85, 0.76 to 0.95). Conclusions Weight gain, weight loss, and intentional weight loss are associated with increased incidence of fracture, but associations differ by fracture location. Clinicians should be aware of fracture patterns after weight gain and weight loss.